2006
DOI: 10.1074/jbc.m512840200
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Synthesis Induces Microvillus-like Cell Surface Protrusions

Abstract: Hyaluronan synthases (HASs) are plasma membrane enzymes that simultaneously elongate, bind, and extrude the growing hyaluronan chain directly into extracellular space. In cells transfected with green fluorescent protein (GFP)-tagged Has3, the dorsal surface was decorated by up to 150 slender, 3-20-m-long microvillus-type plasma membrane protrusions, which also contained filamentous actin, the hyaluronan receptor CD44, and lipid raft microdomains. Enzymatic activity of HAS was required for the growth of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
137
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 53 publications
15
137
1
Order By: Relevance
“…Another study showed that the enzymatic activity of HAS is coupled to plasma membrane residence and the HAS is localized to cell protrusions [30]. In this recent study, HAS overexpression and hyaluronan production was also found to influence the formation of these microvillous protrusions in adenocarcinoma cells and other epithelial cells [31] (Fig. 4).…”
Section: Pericellular Matrix Regulation Of Cell Adhesionmentioning
confidence: 85%
See 2 more Smart Citations
“…Another study showed that the enzymatic activity of HAS is coupled to plasma membrane residence and the HAS is localized to cell protrusions [30]. In this recent study, HAS overexpression and hyaluronan production was also found to influence the formation of these microvillous protrusions in adenocarcinoma cells and other epithelial cells [31] (Fig. 4).…”
Section: Pericellular Matrix Regulation Of Cell Adhesionmentioning
confidence: 85%
“…The GFP-label imaged in live cells reveals that the coat is actually scaffolded by numerous elongated microvilli, on which Has accumulates (Fig. 5) [31]. Similar thin microvilli embedded in HAcoat have been found in untransfected cells such as those of mesothelium, known to synthesize high amounts of HA (unpublished data).The length of the microvilli can exceed 20 μm and they are extremely thin, almost undetectable in ordinary phase contrast microscopy, and easily destroyed during fixation.…”
Section: Hyaluronan Support For Plasma Membrane Protrusionsmentioning
confidence: 90%
See 1 more Smart Citation
“…To investigate the functional consequences of these differences, we studied the effect of the HAS enzyme inhibitor, 4MU, on TGF-␤ 1 -mediated myofibroblastic differentiation in dermal fibroblasts. Depletion of the UDP-glucuronic acid pool by 4MU has been shown to inhibit HA synthesis and pericellular HA coat formation in a number of cell types, including fibroblasts (34,(41)(42)(43)(44). Incubation of dermal fibroblasts with 4MU significantly attenuated both mRNA and protein expression of ␣-sma and resulted in limited cytoskeletal reorganization of filamentous actin.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be formed by newly synthesized HA polymers tethered to the HAS enzymes on the plasma membrane and bound to HA-binding proteins in the matrix. Recent data from Kulti et al (42) has demonstrated that in several cell types, the HA coat can induce and maintain prominent microvilli in cell plasma membranes that rest on filamentous actin. These microvilli were degraded when the pericellular coat was destroyed and were dependent on an intact actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%